Quem conta um conto diminui um ponto: a aplicabilidade do projeto didático de gênero (PDG) no ensino de língua portuguesa para a produção do gênero miniconto - André Alexandre Santos Tavares (2024)
This master's thesis, in the scope of Applied Linguistics, proposes a research project whose aim is to develop and apply a didactic project on text genre (PDG, from the acronym in Brazilian Portuguese) focused on short fiction, with a view to developing language skills through reading and text production in students of a 9th grade group of Elementary School students. To that end, this work is based on fundamental aspects of Portuguese language teaching, as recommended in the National Curricular Parameters (PCN) and in the National Common Curricular Base (BNCC). This thesis is based on the theoretical-methodological paradigms proposed in Sociodiscursive Interactionism, elaborated by Bronckart (1999; 2008), on studies about oral and written genres in the school environment, developed by Schneuwly and Dolz (2004), and on Vygotsky's analysis on learning and development processes through the conceptions of mediation, development zones, and psychological instruments (2007; 2008). Some planned interventions also cover research on the genre of short fiction as defined by Spalding (2008), Rodrigues (2011), and Bueno (2021), including the work on genre-focused teaching projects by Guimarães and Kersch (2012; 2014; 2015). In order to achieve these objectives, this research is organized, methodologically, from intervention-research to data generation. Furthermore, a didactic model for genre was built based on the analysis of 10 texts and a genre-focused teaching project titled, "Quem conta um conto diminui um ponto" ("The one who tells a story takes off one bit", in English). The initial and final productions were analyzed considering the didactic model developed, and the model for text analysis was established according to Sociodiscursive Interactionism. Following the stage of analysis, it was possible to note that results show satisfactory student development regarding their mastery of language skills after genre-focused activities. Thus, we believe the didactic project contributed to students becoming better readers and writers of short fiction, appropriate to the characteristics inherent to the genre.